Analysis of the impact of international trade on employment and wages in the South African fruit industry,1990-2018 - Molepo, Nkoti Solly (My University, 2021)
The study analysed the effects of international trade on employment and wages in the fruit industry of South Africa. However, the study prioritised six industries within the fruit industry which are pertinent contributors to economic growth, international trade, employment and source of wages. The six types of fruits considered for this study are apples, apricots, avocadoes, oranges, pears and table grapes. The relationship between international trade and labour market is continuously significant, especially with increasing number of trade agreements amongst countries and regions. The international trade has been identified by many economic authors to be amongst main contributors of employment and wage source in the exporting countries. The overarching theoretical framework guiding research on the impact of international trade on employment and wages is based on Krugman’s theory of imperfect competition. The theory states that international trade on similar products amongst developed and developing countries works in favour of the developed countries based on the following arguments: developing countries export primary commodities; developed countries export beneficiated goods; firms in developed countries are mostly vertically integrated with a higher market share. The overall aim of the study is to analyse the effects of international trade on employment and wages in the South African fruit industry between the period between 1990 and 2018. There are five objectives for the study and they are broken down as follows: outlining the performance of the South African fruit industry in terms on international trade, employment and wages; secondly, to analyse the impact of international trade flow on employment and wages in the selected six South African fruit industries; thirdly, to determine the causality effects amongst employment, wages and exports within the six South African fruit industry; fourthly, to determine the response of employment, exports and imports on changes in wages within the selected six South African fruit industries; and lastly, to determine the effects of European Union’s Trade Development and Cooperation Agreement on wages in the South African fruit industry. vi The study adopted various analytical techniques to address the objectives. Those analytical techniques were used as follows: descriptive statistics, to profile the six prioritised fruit industries; error correction model, to analyse the impact of international trade flow on employment and wages in the selected six South African fruit industries; granger causality test, to determine the causality effects amongst employment, wages and international trade within the six South African fruit industry; two-staged least squares approach, to determine the response of employment, exports and imports on changes in wages within the selected six South African fruit industries and ordinary least squares, to determine the effects of European Union’s Trade Development and Cooperation Agreement on wages in the South African fruit industry. The findings from descriptive analysis show that all six prioritised fruit industries contributes significantly to the international trade, employment and wages in South Africa. The error correction model for all six fruit industries indicates the existence of a long-run relationship amongst total employment, wages and international trade. Therefore, findings for all fruit industries show that exports output lead to an increase in total employment in a long run, while imports output lead to a decrease in total employment in a long run. The granger causality test for all six fruit industries highlight that there is a causality effect between total employment and exports output. However, there is no causality effect between total employment and imports output, even between exports output and imports output. The results from the two-staged least squares indicate that the wages are affected positively by the exports output. However, there are other factors that affect wages positively such as net realisation from exports, local sales, total gross value of production and foreign direct investment. The wages are negatively affected by imports output, average exchange rate and average prices. The ordinary least squares for all estimated fruit industries show that the volumes of exports to the European Union market affect the wages positively, vii while other variables that are positively affected by the exports to EU market include amongst others the production volumes, productivity, total area planted and foreign direct investment. However, the volumes of exports to the European Union market negatively affect the processing volumes of the fruit industries in South Africa, domestic consumption per capita and average prices. Conclusively, it is recommended that fruit producers, with support of government institutions responsible for trade promotions, should strengthen trade cooperation with various trading blogs, more particularly the European Union; United Kingdom; countries in Asia and Middle East; and African states. This exercise will highly enhance the capacity of South African fruit producers to exploit the untapped international trade opportunities from different markets. Furthermore, it is prudent to recommend that the government should continue to regulate the labour market so that employees could benefit from net realisation from international trade. This will probably reduce the instances of unfair labour practices such as lower wages, child labour, abnormal working hours and overall poor working conditions.
Thesis (Ph. D. Agriculture (Agricultural Economics)) -- University of limpopo, 2021
Keywords: International trade; Employment; Wages; Foreign trade; International trade; Foreign trade and employment; Labor market -- South Africa; Employment (Economic theory); Wages; Fruit trade -- South Africa